The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1111/j.1447-0756.2010.01505.x
|View full text |Cite
|
Sign up to set email alerts
|

Premenstrual disorders in Polish adolescent girls: Prevalence and risk factors

Abstract: Adolescent females living in urban areas are more vulnerable to premenstrual syndrome. Reproductive, sexual and socio-economic factors are not significant risk factors for premenstrual syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
9
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 16 publications
5
9
0
1
Order By: Relevance
“…Sahin et al 8 demonstrated that the PMS prevalence among university students in Turkey was significantly higher among the consumers of coffee, chocolate, and fatty and salty foods; however, we do not have scientific evidence regarding the role of these nutrients in the etiopathogenesis of the syndrome. 16 Half of the students reported performing physical activity two or more times a week, which is similar to the data found in a study with Polish adolescents, 17 but, in the Polish study, there was no positive association between physical activity and PMS symptoms. 17 In addition, the Sahin et al 8 study in Turkey found an even greater frequency of PMS in women who practiced physical activity regularly, which suggests that the physical activity would not have been sufficient to produce beneficial effects on PMS.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Sahin et al 8 demonstrated that the PMS prevalence among university students in Turkey was significantly higher among the consumers of coffee, chocolate, and fatty and salty foods; however, we do not have scientific evidence regarding the role of these nutrients in the etiopathogenesis of the syndrome. 16 Half of the students reported performing physical activity two or more times a week, which is similar to the data found in a study with Polish adolescents, 17 but, in the Polish study, there was no positive association between physical activity and PMS symptoms. 17 In addition, the Sahin et al 8 study in Turkey found an even greater frequency of PMS in women who practiced physical activity regularly, which suggests that the physical activity would not have been sufficient to produce beneficial effects on PMS.…”
Section: Discussionsupporting
confidence: 73%
“…16 Half of the students reported performing physical activity two or more times a week, which is similar to the data found in a study with Polish adolescents, 17 but, in the Polish study, there was no positive association between physical activity and PMS symptoms. 17 In addition, the Sahin et al 8 study in Turkey found an even greater frequency of PMS in women who practiced physical activity regularly, which suggests that the physical activity would not have been sufficient to produce beneficial effects on PMS. Despite this, the practice of regular exercise (at least 30 minutes a day on most days of the week) has been widely recommended for reducing PMS symptoms.…”
Section: Discussionsupporting
confidence: 73%
“…These findings suggested that PMS and PMDD are major problems that affect the daily lives of adolescents, possibly to a larger extent than adults. Although studies have been conducted to investigate the prevalence of PMS and PMDD in adolescents [ 8 11 ], no study has ever revealed how premenstrual symptoms actually affect the school or social life of girls in adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…Premenstrual symptoms might cause several difficulties for female including impairment in physical functioning, psychological health, and severe dysfunction in social or occupational functioning. In young adolescents symptoms might particularly affect school functions and social interactions in a negative way [5][6][7][8]. The overall prevalence reported varies between 30%-90%, with 5-10% reporting severe symptoms [9][10][11].Whatever the cause(s) of PMS, it is clear that the complaints are related to the changes in the hormonal milieu produced by the menstrual cycle, which is itself under the control of the hypothalamic-pituitary-ovarian axis [12].…”
Section: Introductionmentioning
confidence: 99%